Spatial Factors of Social Exclusion and Inclusive Development in Manipur - Sapruna, Lophro Celina (JOURNAL OF INDIAN EDUCATION, 2015)
The present study is an attempt of analytical research on inclusive development and social exclusion of tribal in North-East India with special reference to the state of Manipur. It situates deprivation and exclusion of tribal in both regional and national context. The paper emphasises on the aspects of provisioning and accessibility of tribal communities to different facets of development programmes. Recognising the multiple dimensions of deprivation and vulnerability of the minority groups in contemporary India, this research focuses on the region-specific constraints impeding the process of inclusive growth and development in order to understand the dynamics of exclusive inclusion of the minority tribal communities in Manipur partly as a consequence of spatial disadvantage.